Quality of life and cardiopulmonary variables in patients with pulmonary arterial hypertension in the city of Uruguaiana (RS) (Research, Society and Development, 2020)
Pulmonary Hypertension (HP) is defined as an increase in mean pulmonary artery pressure (PAPm) ≥ 25mmHg at rest, pulmonary vascular resistance (PVR) greater than 4 Wood Units, or when the transpulmonary gradient is greater than 10-12 mm Hg. Causing dyspnea, fatigue, physical deconditioning and muscle weakness leading to worsening quality of life. Therefore, the aim of this study is evaluate quality of life and cardiopulmonary variables in patients with PH. Case series of patients evaluated at the Santa Casa de Caridade de Uruguaiana (RS) from April to June 2018. After the medical assessment, the Short Form 36 (SF-36) quality of life questionnaire was applied. Then, respiratory muscle strength (FMR) was conducted. After a 30-minute rest, patients underwent the 6-minute walk test (6MWT).Two patients were included in the study, mean age 39.5 ± 2.12 years, functional class I according to NYHA modified for PH, which presented values within normal standards in physical and emotional aspects according to the SF-36 questionnaire and in relation to the cardiopulmonary variables (represented by FMR and the 6MWT). Thus, the domains physical and emotional aspects and the cardiopulmonary variables were within the normal values, since the cases of these patients were in the initial stage of the disease.